Association of IGF1 gene polymorphism with Parkinson's disease in a Han Chinese population. (April 2017) - Xiao, Yousheng; Cen, Luan; Mo, Mingshu; Chen, Xiang; Huang, Shuxuan; Wei, Lei; Li, Shaomin; Yang, Xinling; Qu, Shaogang; Pei, Zhong; Xu, Pingyi
Abstract: Background: Accumulating evidence suggests that insulin‐like growth factor 1 ( IGF1 ) plays an important role in Parkinson's disease (PD) pathogenesis. However, it is not clear whether IGF1 polymorphism contributes to PD risk. Methods: We performed a case–control study in a Han Chinese population that included 512 sporadic PD cases and 535 matched controls. All participants were genotyped for rs972936 using the Sequenom MassARRAY iPLEX platform. Serum IGF1 levels of 61 de novo, drug‐naïve PD patients and 55 age‐ and sex‐matched controls were also measured using an enzyme‐linked immunosorbent assay. Results: Genotype frequency of rs972936‐CC was significantly associated with an increased PD risk ( p  = 0.009), especially in males ( p  = 0.024) and late‐onset patients ( p  = 0.013). Serum IGF1 levels were significantly increased in de novo, drug‐naïve PD patients compared to controls ( p  = 0.036), although they were not correlated with motor dysfunction in PD patients ( p  = 0.220). Conclusions: The present study shows that rs972936 polymorphism may increase susceptibility to PD, especially in males and late‐onset patients. Furthermore, high serum IGF1 levels may be a potential diagnostic biomarker for PD in the Han Chinese population, although they do not correlate with a more severe motor dysfunction.